A Inventory of Medicinal Plants in Selilau Village, Aru Tengah District, Aru Islands Regency, Maluku Province - Hastuti, Hastuti (INDIGENOUS BIOLOGI : JURNAL PENDIDIKAN DAN SAINS BIOLOGI, 2023)
Indonesia is a country that has very abundant natural wealth. It is estimated that there are around 35,000 species that grow in Indonesia and 3,500 of them have medicinal properties. the people of Selilau Village in Aru Tengah District, Aru Islands, Maluku Province, have long practiced the use of plants as alternative medicine. This study aims to determine the types of plants used, the organs used and how to use medicinal plants by the people of Selilau Village in Aru Tengah District, Aru Islands, Maluku Province. Data collection was carried out using a semi-open interview method with people who still practice this traditional medicine. Data were analyzed descriptively qualitatively and presented in tabular form. The research results showed that there were 13 types of medicinal plants used by the community to treat various diseases. Plant organs used as medicine are leaves, leaf midribs, roots and all parts of the plant. The organ of the plant that is most widely used is the leaf. How to use medicinal plants that is by boiling, squeezing and paste. The most practiced way of use is by boiling it and then drinking it.